The brief McGraw-Hill handbook - Maimon, Elaine P. (McGraw-Hill Co., 2010)
Drawing on its authors' more than twenty years of research into writing in college, this economy handbook offers extensive technological support and an indispensable resource for learning, writing, researching, and editing. The Brief McGraw-Hill Handbook features practice exercises throughout, a focus on visual rhetoric, content tied to outcomes, grammar diagnostic quizzes, strong coverage of research and plagiarism, extensive support for multilingual writers, a fully integrated online component, and much more.